Digital twin development and deployment on the cloud : developing cloud-friendly dynamic models using Simulink/Simscape and Amazon AWS /: developing cloud-friendly dynamic models using Simulink/Simscape and Amazon AWS. (2020) - Khaled, Nassim; Pattel, Bibin; Siddiqui, Affan
No abstract available